A multi-centre, post-marketing surveillance study of Vi polysaccharide-tetanus toxoid conjugate vaccine (Typbar TCV®) in India - Raghu Reddy; Bhargav Reddy; Vamshi Sarangi; Siddharth Reddy; Raches Ella; Krishna Mohan Vadrevu (Taylor & Francis Group, 2022)
A typhoid Vi capsular-polysaccharide tetanus toxoid conjugate vaccine (Typbar-TCV®) was recommended by the World Health Organization for use in children >6 months of age. The present post-marketing surveillance study was intended to assess the clinical safety of approximately 11 million doses of TCV sold till 2019 in a diverse age range Indian population. Both active and passive post-marketing surveillance studies were conducted at multiple centers. Active surveillance was performed in two periods, Period-I: February to October 2016, Period-II: April 2017 to October 2018. In Period-II, the Brighton Collaboration Criteria adverse event case definitions were used. Passive surveillance was performed from February 2016 to December 2019 through voluntary reporting by pediatricians across India. During the active surveillance, 1147 adverse events were reported among 4,991 (23.0%) subjects in Period-I, and 596 adverse events among 3898 (21.3%) subjects in Period-II. The most frequent adverse events were fever (9.2% and 12.02%in Periods I and II, respectively), pain at the injection site (8.3% and 7.33%), and swelling (4.0% and 1.93%). No serious adverse events (SAEs) were reported during either Period. Passive surveillance revealed 235 adverse events, including 25 SAEs requiring hospitalization, of which two were due to typhoid fever. All the events mentioned above occurred within one week of vaccination, and all the subjects have recovered from AEs with medications. All reported adverse events resolved with no clinical sequelae. Observations in this study are consistent with the pre-licensure studies with no additional safety signals detected, confirming that Typbar-TCV® is safe. Abbreviations: AE: Adverse event; LMIC: low- and middle-income countries; PMS: Post-marketing surveillance; SAE: Serious adverse event; TCV: Vi-polysaccharide tetanus -toxoid conjugate vaccine (Typbar-TCV®)